Psychological Empowerment as a Mediator in the Influence of Perceived Support, Engagement, and Fit on Commitment - Gusti Tia Ardiani; Annas Syams Rizal Fahmi; Elis Listiana Mulyani; Dede Sri Rahayu; Lucky Radi Rinandiyana (Sawala : Jurnal Administrasi Negara, 2026)
The financial services industry is undergoing a digital transformation that requires competent employees with a high level of organizational commitment. Without such support, organizational change risks encountering resistance or even failure. This study aims to analyze the influence of perceived organizational support, employee engagement, psychological empowerment, and person-organization fit on organizational commitment within the financial services sector. This research used a quantitative survey approach. The sample consisted of employees from financial service organizations at Priangan Timur. Data were analyzed using structural equation modeling (SEM) to test the hypothesized relationships among variables. The results shows that perceived organizational support, employee engagement, and person-organization fit significantly affect organizational commitment, with psychological empowerment as a key psychological mechanism that strengthens these effects. These findings highlight the importance of psychological factors and value congruence in fostering employees’ long-term commitment. This study contributes theoretically to the development of organizational commitment models based on psychological approaches and provides practical implications for human resource management in financial services. The findings suggest strategies for effectively managing employees in the era of digital disruption.